2010
DOI: 10.3727/096368910x494911
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Residence Time of Mesenchymal Stromal Cells (MSC) Injected into the Myocardium

Abstract: The therapeutic mechanism of mesenchymal stromal/stem cells (MSC) for the treatment of acute myocardial infarction is not well understood. Our goal was to get insights into this mechanism by analyzing the survival kinetics of allogeneic and syngeneic cell transplants under different tissue conditions. Two MSC cell banks, stably and equally expressing the luciferase reporter construct, were developed for these studies and injected directly to the myocardium of Lewis rat recipients under syngeneic or allogeneic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…In response to these issues, the use of allogeneic MSCs has been proposed on account of their immune‐modulating ability and their relatively low immunogenic phenotype 1, 3. Previous reports have shown that injection of allogeneic MSCs, without immunosuppressive treatment, improved cardiac function to the same extent as autologous (syngeneic) MSCs in experimental myocardial infarction (MI) models 4, 5, 6. Allogeneic MSCs have already been injected in patients with heart failure, and the safety and feasibility (and preliminary effect) of this treatment has been established 7, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to these issues, the use of allogeneic MSCs has been proposed on account of their immune‐modulating ability and their relatively low immunogenic phenotype 1, 3. Previous reports have shown that injection of allogeneic MSCs, without immunosuppressive treatment, improved cardiac function to the same extent as autologous (syngeneic) MSCs in experimental myocardial infarction (MI) models 4, 5, 6. Allogeneic MSCs have already been injected in patients with heart failure, and the safety and feasibility (and preliminary effect) of this treatment has been established 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has also been reported that the immune‐suppressive ability of MSCs observed in in vitro settings is not effective enough for transplanted allogeneic MSCs to establish immune privilege in various disease conditions in vivo 4, 5, 9, 10. Westrich et al observed that ≈1% of total injected allogeneic MSCs survived at day 2 after intramyocardial injection (a similar ratio to syngeneic MSCs, calculated from their data) in a rat subacute MI model, whereas most allogeneic, but not syngeneic, MSCs subsequently disappeared by day 7 4.…”
Section: Introductionmentioning
confidence: 99%
“…Human NIS is non-immunogenic and has restricted expression in the adult body, making NIS an ideal reporter for imaging. While a large number of studies focus on imaging of cells transplants in small animals [167], studies on large animals such as the porcine model, is of significance due to potential translation into clinics [168]. Serial non-invasive tracking of porcine bone marrow-derived mesenchymal stem cells delivered intra-myocardially and monitored by PET showed the presence of viable transplanted cells in porcine myocardium [169].…”
Section: Possible Tumorigenicitymentioning
confidence: 98%
“…Auch diese autologen Zellen sind leicht zugänglich. Es gibt aber bisher nur eingeschränkte Belege ihrer Differenzierbarkeit in Kardiomyozyten [62,63].…”
Section: Zellursprung Für Myokardiales Tissue Engineeringunclassified